2013
DOI: 10.1136/bjsports-2012-091802
|View full text |Cite
|
Sign up to set email alerts
|

Subacromial impingement syndrome—effectiveness of physiotherapy and manual therapy

Abstract: Some physiotherapeutic treatments seem to be promising (moderate evidence) to treat SIS, but more research is needed before firm conclusions can be drawn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 40 publications
3
58
1
1
Order By: Relevance
“…This fact reinforces previous recommendations based on moderate evidence98 and also corroborates with Hallgren et al ,99 which demonstrated that specific exercises reduce the need for surgery. Concerning types of exercises used in the treatment, there were some interesting findings.…”
Section: Discussionsupporting
confidence: 91%
“…This fact reinforces previous recommendations based on moderate evidence98 and also corroborates with Hallgren et al ,99 which demonstrated that specific exercises reduce the need for surgery. Concerning types of exercises used in the treatment, there were some interesting findings.…”
Section: Discussionsupporting
confidence: 91%
“…There is, however, little supporting evidence detailing an optimum period of conservative management. 9,10 Studies have suggested that very specific excercises are required for successful results with conservative management. 1,3 Some responders are therefore justified in raising concerns regarding the availability of appropriate physiotherapy expertise in their practice.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the convex-concave rule which suggests that a superior roll of the convex humerus is accompanied by an inferior glide, caudal mobilizations of the shoulder are often used to address restrictions of glenohumeral abduction (Hsu et al, 2000, Kaltenborn et al, 2002. While there is an ongoing debate about the scientific evidence supporting the coupling of abduction with inferior glide (Graichen et al, 2000, Chopp et al, 2010, inferior mobilization of the humeral head remains a common manual therapy treatment for individuals with shoulder impingement, rotator cuff tear, adhesive capsulitis and bursitis (Senbursa et al, 2007, Lin et al, 2008, Senbursa et al, 2011, Gebremariam et al, 2014.…”
Section: Introductionmentioning
confidence: 99%